TÜRKİYE'DEKİ İKİNCİ EL AÇIK OTO PAZARLARI VE SAMSUN ÖRNEĞİ - ŞİRİN, MÜRŞİT (Fırat Üniveristesi, 2011)
Samsun ili Karadeniz Bölgesinin Orta Karadeniz Bölümünde sahil şeridinin orta kısmında yer almaktadır. Samsun şehri; 400 ? 05' ve 410 ? 44' kuzey enlemleri ile 350 ? 30' ve 370 ? 05' doğu boylamları arasında bulunmaktadır. Kuzeyinde Karadeniz ile sınırlandırılmış olan il batıda Sinop güneybatıda Çorum, güneyde Amasya ve Tokat doğuda ise Ordu illeriyle çevrilmiştir.Çalışma alanının nüfus özelliklerine bakacak olursak; Samsun ilinin nüfusu 2009 yılı nüfus sayımlarına göre 1.250.076 kişidir. Yüzölçümü ise 9.352 km2dir. Samsun şehir merkezi 73 mahalleden oluşmaktadır. Çalışma konusu seçilen 2.el açık oto pazarı ise Samsun il merkezinin doğusunda yer alan Tekkeköy ilçesinde Kirazlık mevkiinde bulunmaktadır.Pazarlar tarih boyunca insanların ortak paylaşım alanları olmuştur. Pazar malların alıcı ile satıcı arasında yer değiştirdiği, ekonomik canlılığın olduğu bir mekandır. Gelişen teknolojiyle beraber araçlar günlük hayatımızda çok önemli bir yere gelmiştir. Öyle ki araçlar galeri ve plazalardan çıkarak ikinci el açık oto pazarlarında alım ve satımı yapılmaktadır.Bu tez çalışmasında beşeri hayatta bu kadar önemli olan araçların ikinci el açık oto pazarları içerisindeki Samsun oto pazarı örneği incelendi. Öncelikle ikinci el açık oto pazarlarının ortaya çıkış sebepleri, pazarları halkın tercih etme nedenleri ve pazardaki araç çeşitleri belirlenmeye çalışıldı. Daha sonra ise Türkiye'deki oto pazarlarının iller ve ilçeler bazında dağılışı gösterildi.Çalışma sahası olan Samsun ilindeki ikinci el açık oto pazarının tarihi gelişimi pazara mevsimlere göre giriş yapan araç sayısı, araç alıcılarının ve satıcılarının genel özellikleri ve Samsun oto pazarının bölge içindeki etki sahası belirlenmeye çalışıldı. Çalışmanın sonunda mevcut durumu daha iyiye ulaştırmak için bazı önerilerde bulunuldu.Anahtar Kelimeler: Pazar, Samsun Şehri, Etki Sahası, Ekonomik Coğrafya, Ulaşım Coğrafyası

Samsun city is located in the middle of the coastal band of the Middle Black Sea part situated in the Black Sea Region. Samsun city is located between 40°-05? and 41°-44?north latitudes and 35°-30? and 37°-05?east longitudes. The city which is bordered with the Black Sea at north is bounded with Sinop at west, with Çorum at south west, with Amasya and Tokat at south and with Ordu at east.When examiningthe population characteristics of the working area ; The population of Samsun city is 1.250.076 according to the population census of year 2009. The surface area is 9.352 km2. The center of Samsun is consisting of 73 quarters. As for the second hand open car market which has been chosen as the study subject is situated at Kirazlık location of Tekkeköy district which is located at the east of the city center of Samsun.The markets have been common sharing areas for humans throughout history. The market is a place where merchandises are changing places between buyers and sellers and where a certain economic vitality is existing. Vehicles have gained a very important place in our everyday life together with the developing technology. Such that vehicles are issuing from showrooms and plazas in order to be buyed and sold at second hand open car markets.In this thesis study we have examined Samsun car market example involved in the subject of second hand open car markets for the vehicles that are so much important for the human life. First of all we have tried to determine the reasons of the emergence of second hand open car markets, the factors that conduce people to opt for markets and the kinds of vehicles existing in the markets. Then we have demonstrated the car markets distribution in Turkey according to cities and districts basis.We have tried to determine historical development of second hand open car market in the Samsun city which is a working area, the number of vehicles that have entered in the market according to the seasons, the general characteristics of vehicle buyers and sellers and the area influence of samsun car market within the region. At the end of the study we have made some suggestions in order to ameliorate the existing situation.Key Words : Market, Samsun City, Influence area, Economic Geography, Transport Geography
Samsun example for second hand car open markets in Turkey
Keywords: İşletme